Adjuvant therapy with pegylated interferon-alfa2b vs observation in stage II B/C patients with ulcerated primary: Results of the European Organisation for Research and Treatment of Cancer 18081 randomised trial. (July 2020) - Eggermont, Alexander M.M.; Rutkowski, Piotr; Dutriaux, Caroline; Hofman-Wellenhof, Rainer; Dziewulski, Peter; Marples, Maria; Grange, Floren; Lok, Catherine; Pennachioli, Elisabetta; Robert, Caroline; van Akkooi, Alexander C.J.; Bastholt, Lars; et al.
Abstract: Background: Subgroup analyses of two large EORTC adjuvant interferon-alpha2b (IFNα-2b) vs observation randomised trials demonstrated that a treatment benefit was observed only in patients with an ulcerated melanoma without palpable nodes (hazard ratio [HR] for recurrence-free survival [RFS] was 0.69). This was confirmed by a meta-analysis of 15 adjuvant IFN trials (HR: 0.79). Patients and methods: In the EORTC 18081 trial, sentinel node-negative stage II patients with an ulcerated primary melanoma were 1:1 randomised between pegylated (PEG)-IFNα-2b at 3 μg/kg/week subcutaneously and observation, for 2 years, or until disease recurrence or unacceptable toxicity in spite of dose adjustments to maintain an Eastern Cooperative Oncology Group performance status of 0 or 1. Main end-point was RFS. Secondary end-points included distant metastasis-free survival (DMFS), overall survival, and safety (EudraCT Number: 2009-010273-20). Results: Between February 2013 and January 2017, only 112 patients were randomised, 56 in each arm. The trial was stopped early for lack of recruitment. At a 3.4-year median follow-up, the estimated HR for the PEG-IFNα-2b group compared with the observation group regarding RFS was 0.66 (95% confidence interval [CI]: 0.32–1.37), and the 3-year RFS rate was 80.0% (95% CI: 65.7–88.8%) and 72.9% (95% CI: 58.3–83.0%), respectively. DMFS was prolonged: HR: 0.39 (95% CI: 0.15–0.97), and the 3-year DMFS rate was 90.6% (95% CI: 78.9–96.0%) vs 76.4% (95% CI: 62.1–85.9%). One patient in the PEG-IFNα-2b group died compared with 4 in the observation group. Fifty-four patients started PEG-IFNα-2b treatment, 16 (29%) completed 2 years of treatment, 2 (4%) stopped due to recurrence, 23 (43%) due to toxicity and 14 (25%) due to other reasons. Conclusions: The EORTC 18081 PEG-IFNα-2b randomised trial, observed a similar HR (0.69) for RFS as the previous EORTC trials (0.69). In countries without access to new drugs, adjuvant (PEG)-IFNα-2b treatment is an option for patients with ulcerated melanomas without palpable nodes. Highlights: Adjuvant PEG-IFNα2b improved the outcomes in ulcerated stage III melanoma. EORTC 18081 in stage II confirmed earlier observations in stage III trials. Adjuvant PEG-IFNα2b improved RFS (HR 0.66) and DMFS (HR 0.39). At 3 years PEG-IFNα2b improved RFS rate by 7.1% and DMFS rate by 14.2%.